Pengembangan Pertanian Organik di Kelompok Tani Madya, Desa Kebonagung, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Firda Emiria; Heru Purwandari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2014)
Organic farming is agricultural activities that seek the use of outside intake and avoid the use of pesticides and synthetic fertilizer. The results showed that the organic farmers and conventional farmers have the high responses of organic farming. However, the characteristics of organic farmer have no relation with farmer’s respons of organic farming. Then, in conventional farmers, formal education and the courage to take the risks have relation with farmer’s respons of organic farming. This research also showed there are no relation between farmer’s respons of organic farming with farmer’s income. Nevertheless, can be predicted that there are chances of the conventional farmers to adopt the organic farming.Keywords: organic farming, respons, income, conventional farmer